Interferon-γ and voriconazole combined therapy for refractory meningeal coccidioidomycosis in a patient with interferon-γ deficiency. (2020) - De la Hoz, Alejandro; Malek, Alexandre; Hasbun, Rodrigo
Highlights: Coccidioides meningitis is a difficult to treat invasive infection. Voriconazole is an option for the treatment of refractory Coccidiodes meningitis. Adjuvant interferon may play an important role in the treatment of refractory Coccidioides meningitis. Abstract: Coccidioides meningitis (CM) is a challenging infection, given the limited penetration to the cerebrospinal fluid of conventional antifungals, resulting in a high risk of recurrence. We present the first case of a successfully treated persistent CM with voriconazole and adjuvant INF-γ 1b.